Strategies for glucose control in a study population with diabetes, renal disease and anemia (Treat study). (March 2016) - Weinrauch, Larry A.; D'Elia, John A.; Finn, Peter; Lewis, Eldrin F.; Desai, Akshay S.; Claggett, Brian L.; Cooper, Mark E.; McGill, Janet B.
Highlights: Choices of antidiabetic therapy with diminished renal function and anemia. Vary according to level of renal function. Are subject to regional variation. Demonstrate greater reliance on insulin at lowest levels of renal function. Abstract: Glucose lowering medication use among patients with type 2 diabetes and advanced renal disease (eGFR < 60) in a large multinational outcome trial (TREAT) is assessed. We demonstrate statistically significant differences regionally in use of metformin at lower eGFR and increasing reliance upon insulin with/without other medications at low eGFR. Introduction: As renal disease advances, most of the oral anti-diabetic agents requiring renal clearance must be reduced or discontinued. The potential for prolonged hypoglycemia, fluid/volume overload and congestive heart failure may complicate medication choices. In order to evaluate patterns of glycemia management we describe glucose lowering medication use among patients with advanced renal disease and type 2 diabetes in a large multinational outcome trial designed to focus on patients with eGFR < 60 in order to commence a dialog on best practices. We felt that analysis of this data would be able to describe regional variations in treatment within a multinational trial in order to understand potential outcome differences attributed to complications. Results: The patients entering this study had moderate glycemic control. Insulin therapy either alone (32%) or in combination with other agents (17%) reflected a shift towards insulin use in those subjects with decreased renal function when compared with standard populations with normal kidney function. The use of multiple oral agents, or oral agents plus insulin was quite common. While gender did not appear to play a role in medication choices, there were significant regional variations. For example, oral agents were used more in North America compared with other regions (Latin America, Australia/Western Europe, Russia/Eastern Europe). Patients enrolled at more advanced ages were less likely to be on a regimen of rapid-acting insulin alone consistent with recommendations that suggest a preference for longer-acting preparations in the geriatric population (1). Higher degrees of obesity were associated more complex treatment regimens. Despite this population being at high risk for cardiovascular events, the use of beta blockers (50%), statins (64%) and aspirin (48%) were relatively low, especially in the group that did not require medications to achieve adequate glycemic control. Conclusions: Current attempts to compare strategies for diabetes therapy must control for baseline demographic group differences influencing treatment choice. Future recommendations for glycemic control in patients with Grade 3 or higher chronic kidney disease require additional studies, with matched populations. We suggest that evaluation of studies similar to TREAT will assist in determining the optimal therapeutic regimens for populations with moderate to severe renal dysfunction, a condition in which repeated hospitalizations for fluid overload/heart failure add to the high cost of diabetes care.